The Great War for Civilisation the conquest of the Middle East - Fisk, Robert (London Harper Perennial, 2006)
A sweeping and dramatic history of the last half century of conflict in the Middle East from an award-winning journalist who has covered the region for over thirty years, The Great War for Civilisation unflinchingly chronicles the tragedy of the region from the Algerian Civil War to the Iranian Revolution; from the American hostage crisis in Beirut to the Iran-Iraq War; from the 1991 Gulf War to the American invasion of Iraq in 2003. A book of searing drama as well as lucid, incisive analysis, The Great War for Civilisation is a work of major importance for today's world.
Includes index
Keywords: War--History.